The impact of thin trading adjustments on exchange rate exposure - Jaratin Lily; Imbarine Bujang; Abdul Aziz Karia (Universitas Gadjah Mada, 2022)
This study investigates the multiple exchange rate exposure of large non-financial firms in Asia and emerging countries using the unadjusted and adjusted two-factor exchange rate exposure model. The autoregressive-distributed lag (ARDL) method was applied to investigate the existence of exchange rate exposure. The Dimson-Fowler-Rorke (DFR) adjustment method was applied to adjust the ordinary least squares (OLS) market risk estimator for the thin trading phenomenon. The study’s findings indicate that exchange rate exposure does affect firm value. Incorporating the DFR market beta in the exchange rate exposure model indicates two important findings. Firstly, there is a significant increase in the number of firms exposed to exchange rate movements, especially in Indonesia, Thailand, Sri Lanka, and Vietnam. Secondly, there are more firms that will be exposed to multi bilateral exchange rate exposure across the sample countries. The findings imply that market characteristics such as thin trading could be an alternative explanation of the exchange rate exposure puzzle. Furthermore, future research should include asymmetric analysis as an alternative explanation for exchange rate exposure.